The Implementation of Course Timetable Organizer in UTHM - Tan, Hong Ming; Darman, Rozanawati (Applied Information Technology And Computer Science, 2024)
UTHM Course Timetable Organizer is a web-based timetable system for University Tun Hussein Onn to present information regarding timetable. The purpose of developing this system is to overcome the course conflict issues and optimize the process of timetable generation. This system had solved those issues by having timetable making module which any course conflict will cause warning to alert user. This system is also connected with database which the data can be saved. The different authorization level of user such as staff, lecturer and student helps to access difference needed modules. For staff who also the admin, section allocation module prepared to assign section for faculty course in a more systematical way instead of passing word by stage from staff to lecturer to student. While, student timetable checking module helps lecturer to monitor correctness of timetable for student under advising. Meanwhile, the system also provide history timetable module for student side to check previously generated timetable. This project is implemented waterfall methodology and developed using Hypertext Markup Language (HTML), Hypertext Preprocessor (PHP), JavaScript (JS), and Cascading Style Sheets (CSS) in Visual Studio Code. This course timetable organizer system is expected to help UTHM students to able generate their own timetable errorless